2022
DOI: 10.1177/20499361221128091
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biological consequences of respiratory syncytial virus genetic diversity

Abstract: Respiratory syncytial virus (RSV) is one of the most common etiological agents of global acute respiratory tract infections with a disproportionate burden among infants, individuals over the age of 65, and immunocompromised populations. The two major subtypes of RSV (A and B) co-circulate with a predominance of either group during different epidemic seasons, with frequently emerging genotypes due to RSV’s high genetic variability. Global surveillance systems have improved our understanding of seasonality, dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 163 publications
(205 reference statements)
0
19
0
Order By: Relevance
“…Deep sequencing approaches subsequently helped to broader define RSV diversity, although still only a relatively limited number of sequence data is publicly available. Up to now, 37 genotypes have been identified for RSV B and 13 for RSV A, mainly based on genetic variation in the G glycoprotein (reviewed in [ 25 ]). It was reported that the evolutionary rate for both subtypes differs from each other, with a lower rate of nucleotide substitutions/site/year for RSV A than RSV B [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Deep sequencing approaches subsequently helped to broader define RSV diversity, although still only a relatively limited number of sequence data is publicly available. Up to now, 37 genotypes have been identified for RSV B and 13 for RSV A, mainly based on genetic variation in the G glycoprotein (reviewed in [ 25 ]). It was reported that the evolutionary rate for both subtypes differs from each other, with a lower rate of nucleotide substitutions/site/year for RSV A than RSV B [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although rapid evolution of antigenically variable mucosal viruses like influenza A viruses 35 and SARS-CoV-2 complicate next-generation vaccine design, other mucosal-only respiratory viruses, such as RSV, have shown much less antigenic plasticity 36 , 37 , 38 ; however, it still causes repeated infections over a lifetime without the development of long-term protective immunity. 39 , 40 Thus, although genetic and antigenic variability of viruses like influenza and SARS-CoV-2 make vaccine design more challenging, these factors by themselves cannot fully explain the lack of elicitation of long-term protective immunity against other respiratory mucosal viruses like the more phenotypically stable RSV.…”
Section: Introductionmentioning
confidence: 99%
“…This review revises our understanding of the general pathophysiological features of RSV infection and the experimental default lines that exist for therapeutic development against it [ 30 , 31 ]. Moreover, we mainly discuss different vaccination and therapeutic developments in the domain of RSV clinical management and the understanding of the lack of market approval for these tested drugs [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. After reading this article, the audience will be able to understand the gaps in the literature and clinical developments that need to be undertaken via integrated and collaborative clinical research efforts so that RSV and associated infections can be well managed in the next couple of years.…”
Section: Introductionmentioning
confidence: 99%